Differentiation of UK endemic strains of Salmonella enterica serovar Newport from epidemic North American strains by PCR detection of a truncated bapA chromosomal gene. (February 2016) - Horton, R.A.; Card, R.; Randall, L.P.; Teale, C.J.
Abstract: The aim of this study was to develop a PCR test to detect chromosomal differences between epidemic multidrug resistant (epi-MDR) strains of Salmonella enterica serovar Newport (S. Newport) and non-epi-MDR strains of S. Newport that are endemic to the United Kingdom (UK). Sequence analysis of the biofilm-associated protein A gene ( bapA ) showed that epi-MDR strains of S. Newport from the United States of America (USA) had a deletion of 309 bp, which was not present in non-epi-MDR strains of S. Newport from the UK. A PCR test was developed using primers designed to target this difference and was applied to a panel of S. Newport isolates comprising of strains from the UK (n = 20, non-epi-MDR), from the USA (n = 10, epi-MDR) and from Canada (n = 7). A second panel of isolates (n = 73) was used to assess the test specificity, and these isolates consisted of non-Newport Salmonella serovars (n = 25), and other epidemic serovars (n = 48). Epi-MDR S. Newport isolates produced a characteristic 505 bp amplicon, whereas non-epi-MDR S . Newport isolates produced an 814 bp amplicon. The bapA PCR has potential to discriminate between these S. Newport strains irrespective of their carrying resistance genes. Highlights: A PCR test to discriminate between strains of Salmonella enterica serovar Newport The test targets differences in the gene for biofilm-associated protein A ( bapA ). A 309 bp deletion in bapA of the epidemic-multi-drug-resistant strains of S. Newport This deletion may be a factor influencing the virulence of these strains.